Antioxidant Enzymatic Defences during Embryogenesis of Rainbow Trout Oncorhynchus mykiss (Walbaum 1792) - Zengin, Hatayi; Yilmaz, Okkes; Demir, Ersin; Gokce, Zehra (Central Fisheries Research Inst, 2015)
In this study antioxidant enzymes activities such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSHpx), glutathione reductase (GR) and glutathione S-transferase (GST) were investigated in unfertilized and fertilized eggs, 12, 22 and 32 day embryos of rainbow trout Oncorhynchus mykiss (Walbaum 1792). Vitamin E, lipid peroxidation products and fatty acids levels were also determined. A significant decrease in vitamin E level was found in fertilized eggs of O. mykiss. In contrast, the level of malondialdehyde (MDA) was very high in fertilised eggs and 12 day embryo. The PUFA contents in fertilized eggs and 12 day embryo were found to be lower than in the other embryonic stages. Measurable amounts of all the SOD, CAT, GSHpx, GR and GST enzymes activities were present in O. mykiss eggs and embryos. The most intense decrease was detected in the activities of SOD, GR and GST in fertilized eggs, whereas the most intense increase in the CAT activity was detected in the same stage of O. mykiss. GSHpx activity showed a significant increase in fertilized eggs and in 32 day embryos before hatching. GST activity showed the most significant increase in 22 day embryos of eyed eggs stage.
Gökkuşağı alabalığı Oncorhynchus mykiss (Walbaum 1792)’in embriyonik gelişimi esnasında enzimatik antioksidan savunma
Keywords: Superoxide dismutase; catalase; glutathione peroxidase; glutathione reductase; glutathione S-transferase; vitamin E; embryo; lipid peroxidation